Solar modulation of GCR electrons over the 23rd solar minimum with PAMELA. (July 2015) - Munini, R; Di Felice, V; Adriani, O; Barbarino, G C; Bazilevskaya, G A; Bellotti, R; Boezio, M; Bogomolov, E A; Bongi, M; Bonvicini, V; Bottai, S; Bruno, A; et al.
Abstract: The satellite-borne PAMELA experiment has been continuously collecting data since 15th June 2006, when it was launched from the Baikonur cosmodrome to detect the charged component of cosmic rays over a wide energy range and with unprecedented statistics. The apparatus design is particularly suited for particle and antiparticle identification. The PAMELA experiment has measured the electron spectrum at Earth in great detail, extending up to about 100 GeV and down to about 200 MeV. The galactic cosmic ray electron spectra for 2007 and 2009, i.e. measured during the A<0 solar minimum of solar cycle 23, are presented. These fluxes provide important information for the study of charge dependent solar modulation effects.